Comparative assessment of health risks and water quality of groundwater in urban and rural Guiyang, Southwest China: Insights from PMF and Monte Carlo Simulation - Tingting Zhu; Qixin Wu; Shilin Gao; Jie Zeng; Keli Linghu; Xindi Zhang (Ecotoxicology and Environmental Safety)
Groundwater is a vital resource for socio-economic development. However, rapid urbanization and intensive agriculture have introduced significant trace elements into groundwater, potentially compromising water quality and public health. To evaluate the sources, behavior, and risks of associated with nine trace elements in groundwater, a comprehensive investigation was conducted in both urban and rural areas of Guiyang, a typical karst city in southwest China. The results indicated that most dissolved trace element concentrations (Ti, Mn, V, Co, Ni and Sr) follow a pattern in which urban area exhibit higher levels than rural areas near suburban region, which in turn exhibit higher levels than rural areas far from urban center. The heavy metal pollution index revealed moderate pollution in 6.9 % of urban groundwater samples. Health risk assessment based on Monte Carlo simulation suggested that the non-carcinogenic risks were negligible. However, the total carcinogenic risk cannot be ignored, primarily due to Cr and Ni. Positive matrix factorization analysis identified natural inputs (e.g., rock weathering) as the major sources of V (81.36 %) and Sr (69.59 %). Urban wastewater contributed 36.62–47.55 % of Ti, Co, and Ni, while industrial and traffic waste accounted for 67.56 % and 32.17 % of Ba and Mn, respectively. Furthermore, agricultural activities were responsible for 52.12 % of Zn and 64.42 % of Cr. These findings provide essential baseline data for groundwater management, highlighting the impact of various anthropogenic activities across regions on trace elements in groundwater.